2020
DOI: 10.3390/app10155135
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Applied to Diagnosis of Human Diseases: A Systematic Review

Abstract: Human healthcare is one of the most important topics for society. It tries to find the correct effective and robust disease detection as soon as possible to patients receipt the appropriate cares. Because this detection is often a difficult task, it becomes necessary medicine field searches support from other fields such as statistics and computer science. These disciplines are facing the challenge of exploring new techniques, going beyond the traditional ones. The large number of techniques that are emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 184 publications
(264 reference statements)
0
34
0
Order By: Relevance
“…In Ref. [17], authors have presented a study to diagnose heart diseases, AIDS, brain cancer, diabetes, dengue, and hepatitis C. e machine-learning algorithms, Naive Bayes, J48, K-Nearest Neighbors, and C4.5 algorithms, have been employed to map the patients onto different classes of the above-stated diseases. e comparisons of the results among harnessed classifiers have revealed that C4.5 outperformed with 83.6% prediction accuracy, followed by J48 and Naive Bayes classifiers achieving 81.1% and 75.97% prediction accuracies, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…In Ref. [17], authors have presented a study to diagnose heart diseases, AIDS, brain cancer, diabetes, dengue, and hepatitis C. e machine-learning algorithms, Naive Bayes, J48, K-Nearest Neighbors, and C4.5 algorithms, have been employed to map the patients onto different classes of the above-stated diseases. e comparisons of the results among harnessed classifiers have revealed that C4.5 outperformed with 83.6% prediction accuracy, followed by J48 and Naive Bayes classifiers achieving 81.1% and 75.97% prediction accuracies, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, Caballé et al (2020) believe that technology is currently well suited for analyzing medical data and presents a wide range of possible applications. Unlike early A.I.…”
Section: Discussion Observationsmentioning
confidence: 99%
“…According to Caballé et al (2020) in Artificial Intelligence, Machine Learning stands out as a method for providing tools for intelligent data analysis. There are specific algorithms that are used to develop models with predictive capabilities, and the selection of such algorithms depends on the research objective.…”
Section: Data Analysis Machine Learning Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results from the testing phase, error rate and misclassification are calculated [1]. One of the most popular purposes for which ML has been applied is forecasting [2][3][4][5]. Several ML algorithms have been used to predict future events in applications such as weather forecasting and disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%